2022
DOI: 10.1109/jestpe.2021.3064702
|View full text |Cite
|
Sign up to set email alerts
|

Voltage Distribution in the Windings of Medium-Frequency Transformers Operated With Wide Bandgap Devices

Abstract: The short rise time observed in the PWM voltages generated by ultra-fast wide bandgap devices increases the amplitude of voltage harmonics at higher frequencies. These harmonics can excite the resonances of Medium-Frequency Transformers (MFTs), resulting in overvoltages inside the windings during continuous operation. Without further measures, these overvoltages can lead to unexpectedly high electric fields in the insulation material, which can result in partial discharge, accelerated ageing and possible failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 68 publications
(101 reference statements)
0
13
0
Order By: Relevance
“…The voltage potential distribution of inductors under different frequencies is not verified by experiments in this paper, since the parasitic capacitance of probes and scopes can significantly influence the measured voltage distribution [26]. Therefore, the actual voltage potential distribution of inductors cannot be obtained using voltage probes directly.…”
Section: Experimental Verificationsmentioning
confidence: 86%
“…The voltage potential distribution of inductors under different frequencies is not verified by experiments in this paper, since the parasitic capacitance of probes and scopes can significantly influence the measured voltage distribution [26]. Therefore, the actual voltage potential distribution of inductors cannot be obtained using voltage probes directly.…”
Section: Experimental Verificationsmentioning
confidence: 86%
“…The dominating phenomena in the transformer behavior is mainly dependent on its magnetic coupling. However, the self and mutual resistances must be added to the impedance matrix to account for all kinds of electromagnetic interactions in MFT windings [9]. A six-step FEM analysis is required to establish the symmetric impedance matrix of the system under study shown in Fig.…”
Section: Windingsmentioning
confidence: 99%
“…To check for any undesired impact of the resonances observed from Fig. 15, we compare the first series resonance frequency with the envelope of the PWM voltage applied to the transformer, as suggested in [92]. The spectral envelope of a symmetric PWM voltage with a fundamental period of T s = 1/f s and equal rise time (t r ) and fall time (t f ), see Fig.…”
Section: A Impedance Measurements and Resonancesmentioning
confidence: 99%